JAK Inhibitors and Modulation of B Cell Immune Responses in Rheumatoid Arthritis - Moura, Rita A.; Fonseca, João Eurico (Frontiers in Medicine, 2021)
Rheumatoid arthritis (RA) is a chronic, systemic immune-mediated inflammatory disease that can lead to joint destruction, functional disability and substantial comorbidity due to the involvement of multiple organs and systems. B cells have several important roles in RA pathogenesis, namely through autoantibody production, antigen presentation, T cell activation, cytokine release and ectopic lymphoid neogenesis. The success of B cell depletion therapy with rituximab, a monoclonal antibody directed against CD20 expressed by B cells, has further supported B cell intervention in RA development. Despite the efficacy of synthetic and biologic disease modifying anti-rheumatic drugs (DMARDs) in the treatment of RA, few patients reach sustained remission and refractory disease is a concern that needs critical evaluation and close monitoring. Janus kinase (JAK) inhibitors or JAKi are a new class of oral medications recently approved for the treatment of RA. JAK inhibitors suppress the activity of one or more of the JAK family of tyrosine kinases, thus interfering with the JAK-Signal Transducer and Activator of Transcription (STAT) signaling pathway. To date, there are five JAK inhibitors (tofacitinib, baricitinib, upadacitinib, peficitinib and filgotinib) approved in the USA, Europe and/ or Japan for RA treatment. Evidence from the literature indicates that JAK inhibitors interfere with B cell functions. In this review, the main results obtained in clinical trials, pharmacokinetic, in vitro and in vivo studies concerning the effects of JAK inhibitors on B cell immune responses in RA are summarized.